Proprioception‐related gene mutations in relation to the aetiopathogenesis of idiopathic scoliosis: A scoping review - Lau, Kenney K. L.; Law, Karlen K. P.; Kwan, Kenny Y. H.; Cheung, Jason P. Y.; Cheung, Kenneth M. C. (Journal of orthopaedic research, 2023)
Since idiopathic scoliosis is a multifactorial disorder, the proprioceptive defect is considered one of its etiological factors. Genetic studies have separately revealed this relationship, yet it remains indeterminate which specific genes that related to proprioception contributed to the initiation, progression, pathology, and treatment outcomes of the curvature. A systematic search was conducted on four online databases, including PubMed, Web of Science, Embase, and Academic search complete. Studies were included if they involved human or animal subjects with idiopathic scoliosis and evaluated with proprioceptive genes. The search period was the inception of the database to February 21, 2023. Four genes (i.e., Ladybird homeobox 1 [LBX1], Piezo type mechanosensitive ion channel component 2 [PIEZO2], Runx family transcription factor 3 [RUNX3], and neurotrophin 3 [NTF3]) investigated in 19 studies were included. LBX1 has confirmed the correlation with the development of idiopathic scoliosis in 10 ethnicities, whereas PIEZO2 has shown a connection with clinical proprioceptive tests in subjects with idiopathic scoliosis. However, curve severity was less likely to be related to the proprioceptive genes. The potential pathology took place at the proprioceptive neurons. Evidence of proprioception‐related gene mutations in association with idiopathic scoliosis was established. Nevertheless, the causation between the initiation, progression, and treatment outcomes with proprioceptive defect requires further investigation.